Should universities train teachers for employability or for effectiveness?. (February 2020) - Espinoza, Oscar; González, Luis Eduardo; McGinn, Noel; Sandoval, Luis; Castillo, Dante
Abstract: In principle, the learning sought by universities is universal; that sought by employers of their graduates is contextual. This study illustrates this contradiction in Chile. The three participating universities differ in the socio-economic level of those admitted to teacher training. Teachers for schools in lower-income areas hired from less selective universities are seen by employers as having more skills in classroom management. Schools that enroll middle and upper-income students, on the other hand, hire teachers strong in academic knowledge from the most selective university. This reliance on employability as an indicator of quality of training sharpens social and economic inequalities. Highlights: Employers from lower-income sectors prefer lower-income graduates, because they presume higher class management skills. Employers from higher income sectors prefer higher income graduates, because they presume higher academic knowledge. The recruitment and education of teachers in Chile reproduces social inequalities. Emphasis on employability may have negative consequences for Chile as a society.